A versatile sea anemone-inspired strategy toward 2D hybrid porous carbons from functional molecular brushes. Issue 12 (14th January 2021) - Lin, Xidong; Wang, Zelin; Liu, Ruliang; Liu, Shaohong; Leng, Kunyi; Lou, He; Du, Yang; Zheng, Bingna; Fu, Ruowen; Wu, Dingcai
Abstract : A versatile sea anemone-inspired functional molecular brush is utilized to fabricate 2D hybrid porous carbon. Abstract : A generalized and facile strategy toward 2D hybrid porous carbons (2DHPCs) with various highly active functional species ( e.g. Co, B, and P) is developed via 2D molecular brushes as biomimetic building blocks. The resulting 2DHPCs present superior electrochemical energy conversion and storage properties.